Health and Academic Achievement 2018
DOI: 10.5772/intechopen.72993
|View full text |Cite
|
Sign up to set email alerts
|

Stress in Nursing University Students and Mental Health

Abstract: Stress is a physiological response that impacts the cognitive, emotional, behavioral, and social components. It also involves the adaptation of the organism, the coping resources, and the environment. In young people, stress can be triggered by social interactions or school requirements. This chapter is a narrative review analyzing scientific bibliography from the main databases (NIH, Scielo, Redalyc) that explored the main stressors and their effects on nursing students. These stressors include the care of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 67 publications
2
15
0
Order By: Relevance
“…About the reasons for joining the college, we find that the most selected answer was a work with a good future. This explains the turnout of male nursing colleges more than females and in recent years it is consistent with (6) who described the many benefits of the nursing profession.…”
Section: Discussionsupporting
confidence: 83%
“…About the reasons for joining the college, we find that the most selected answer was a work with a good future. This explains the turnout of male nursing colleges more than females and in recent years it is consistent with (6) who described the many benefits of the nursing profession.…”
Section: Discussionsupporting
confidence: 83%
“…This study shows the significant correlation between perceived level of stress and physio-psycho-social health, results of the study supported by a research results showed that nursing students' pressure adapting levels were influenced without anyone else regard and social help. Also, this connection seems to influence general wellbeing status (Yıldırım, Karaca, Cangur, Acıkgoz, & Akkus, 2017).Results revealed the significant correlation between different academic stress level and emotional, physiological and social responses of students, study supported by the research findings of Frank and Pulido which shows that academic stress can cause physiological and psychological stress which may develop mental disorder (Pulido-Criollo et al, 2017). Findings of this study demands for a bigger task for nurse professors in scheduling plans to avoid relapse of stress among students while keeping them inspired to achieve for a better education.…”
Section: Discussionsupporting
confidence: 63%
“…As study show Stress is a physiological reaction that impacts the intellectual, emotional, conduct, and social segments. It additionally includes the adjustment of the life form, the adapting assets, and environment (Pulido-Criollo, Cueto-Escobedo, & Guillén-Ruiz, 2017) Nursing education is an important part of clinical learning. During clinical learning nursing students face many stressors like lack of professional knowledge, teacher's behavior, assignments and workload.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the experiences of how faculty staff on health and social care programmes support HE students' mental health needs are also under-researched. This is of critical importance to understand as students on healthcare programmes, such as nursing, midwifery, paramedics and social work need additional support to manage and cope with emotionally challenging situations in their practice learning (Pulido-Criollo et al, 2017;Coffey et al, 2014). They need support and opportunities to reflect and talk about these experiences.…”
Section: Faculty Staff Perspectivesmentioning
confidence: 99%